Strain relaxation due to V-pit formation in In[sub x]Ga[sub 1−x]N∕GaN epilayers grown on sapphire - Song, T. L. (2005)
Strain relaxation in semiconductor heterostructures generally occurs through the motion of dislocations that generates misfit dislocations above a critical thickness. However, majority of the threading dislocations in GaN-related materials have no driving force to glide, and those with a driving force are kinetically impeded even at a temperature of 1000 degrees C. In spite of this, the strain in InxGa1-xN/GaN epilayers grown on c-plane sapphire substrates was observed to decrease as the InxGa1-xN layer becomes thicker. We have explored the possibility of V-pit formation at terminated dislocations as the predominant relaxation mechanism in highly mismatched systems such as InxGa1-xN/GaN. We demonstrate that a driving force exists to nucleate V pits for strain relief. The formation of V pits was modeled through the energy balance between the strain energy in the InxGa1-xN epilayer, the destruction of dislocation energy to form V pits and the strain that is relieved due to the formation of edges during the process of nucleating V pits in thermal equilibrium. V-pit formation and growth lead to strain relief as the film becomes thicker. The model illustrates many features that correlate reasonably well with experimental observations; the most significant trends are a rise in V-pit density and a decrease in strain with increasing layer thickness. (c) 2005 American Institute of Physics.